Measurement of the B-0 and B+ meson masses from B-0 ->psi((')) K-S(0) and B+->psi((')) K+ decays - Csorna, SE; Danko, I; McLean, K; Marka, S; Xu, Z; Godang, R; Kinoshita, K; Lai, I; Schrenk, S; Bonvicini, G; Cinabro, D; Perera, L; et al. (2000)
Using a sample of 9.6 × 106BB̄ meson pairs collected with the CLEO detector, we have fully reconstructed 135 B0→ψ(′)KS0 and 526 B+→ψ(′)K+ candidates with very low background. We fitted the ψ(′)K invariant mass distributions of these B meson candidates and measured the masses of the neutral and charged B mesons to be M(B0)=5279.1±0.7[stat]±0.3[ syst] MeV/c2 and M(B+)=5279.1±0.4[stat]±0.4[ syst] MeV/c2. The precision is a significant improvement over previous measurements. ©2000 The American Physical Society.